Illocutionary Speech Acts in the Poem Ayyuha al-Nas by Tamim al-Barghouti - Yaumal Fikri; Zulkhairi; Rizki Rinaldi (Pusaka Cendekia Indonesia Foundation, 2025)
This study analyzes the act of illocution speech in the poem